ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL) PADA PT BANK RAKYAT INDONESIA TBK PERIODE 2018-2024 - Intan Dara Permata (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the financial soundness of PT Bank Rakyat Indonesia (Persero) Tbk using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) framework over the 2018–2024 period. This period captures significant economic dynamics, including the pre-pandemic phase, the COVID-19 pandemic, and the post-pandemic recovery phase. A quantitative descriptive method is employed using secondary data derived from annual financial reports and Good Corporate Governance (GCG) reports. The analysis utilizes Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) as proxies for Risk Profile, GCG self-assessment scores, Return on Assets (ROA) and Net Interest Margin (NIM) for Earnings, and Capital Adequacy Ratio (CAR) for Capital. The findings are expected to provide a comprehensive assessment of the bank’s ability to manage risks, implement sound governance practices, generate sustainable profitability, and maintain adequate capital resilience amid fluctuating economic conditions. This study contributes to the existing literature by offering a longitudinal evaluation of bank soundness using the RGEC approach and provides practical implications for management, investors, and regulators in making strategic decisions based on banking performance and stability.